A baseline of copper associated with antifouling paint in marinas within a large fjord estuary. (May 2022) - Hobbs, William O.; McCall, Melissa; Lanksbury, Jennifer; Seiders, Keith; Sandvik, Patti; Jones, Meredith; Chuhran, Heidi; Momohara, Dean; Norton, Dale
Abstract: Marinas have been shown to contribute elevated concentrations of copper (Cu) to marine waters. The Cu can come primarily from antifouling paints which are designed to discourage biofouling of boat hulls. Legislation in Washington State, USA is being developed to limit or regulate the amount and rate of diffusion of Cu from antifouling paints. This study provides baseline data for Cu in five marinas of different configuration and size within Puget Sound, a large fjord estuary. Samples were collected over a year from multiple environmental media. We find strong evidence that Cu accumulates inside marinas to higher concentrations than outside marinas. Marinas that are more enclosed accumulated higher concentrations of Cu than more open marinas. Using a power analysis, we assessed the adequacy of the baseline dataset to measure progress as a result of future legislation towards the reduction of Cu to Puget Sound from marinas. Highlights: Antifouling paint can introduce copper into marine waters. Copper (Cu) accumulates inside marinas regardless of how enclosed they are. Transplanted mussels do not appear to accumulate Cu in marinas. Cu is bound to suspended sediment and algae and deposited on the marina bottom. Baseline data have been compiled to evaluate the effectiveness of future legislation.